2013
DOI: 10.1177/0192623313492248
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of Lethal and Sublethal Doses of Aerosolized Ricin in Rhesus Macaques

Abstract: Ricin toxin, a type 2 ribosome inactivating protein and a category B bioterrorism agent, is produced from the seeds of castor oil plant (Ricinus communis). Chronic pathological changes in survivors of aerosolized ricin exposure have not been reported in primates. Here we compare and contrast the pathological changes manifested between rhesus macaques (RM) that succumbed to lethal dose of ricin (Group I) and survivor RM exposed to low dose of ricin (group II). All animals in group I exhibited severe diffuse, ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(84 citation statements)
references
References 29 publications
(50 reference statements)
3
81
0
Order By: Relevance
“…Over the past few years, studies of RT aerosols in rhesus macaque (Macaca mulatta) have suggested that these animals are a suitable model for vaccine development. 2 Upon aerosol exposure to supra-lethal doses of RT, macaques develop massive pulmonary edema with necrotizing alveolitis that mainly affects the lower respiratory tract from terminal bronchioles to alveoli.…”
Section: Protective Efficacy Of Rivax In Rhesus Macaquesmentioning
confidence: 99%
See 3 more Smart Citations
“…Over the past few years, studies of RT aerosols in rhesus macaque (Macaca mulatta) have suggested that these animals are a suitable model for vaccine development. 2 Upon aerosol exposure to supra-lethal doses of RT, macaques develop massive pulmonary edema with necrotizing alveolitis that mainly affects the lower respiratory tract from terminal bronchioles to alveoli.…”
Section: Protective Efficacy Of Rivax In Rhesus Macaquesmentioning
confidence: 99%
“…Yet we also know that much of the syndrome associated with exposure to RT and other toxins is due to an acute inflammatory response. 2,[20][21][22] It is not yet known how antibodies, which are themselves proinflammatory, block the proinflammatory activity of the toxin, rather than enhancing it. We can partially address this question by comparing inflammatory responses in immunized macaques with those observed in the controls.…”
Section: Effects Of Immunization On Intoxication and Lung Pathology Imentioning
confidence: 99%
See 2 more Smart Citations
“…Ricin poisoning can cause severe tissue damage, inflammatory reactions, and blockage of protein synthesis, and thus result in cell death [1,2]. In spite of intensive biomedical research, no treatment is at present available for ricin poisoning [3].…”
Section: Introductionmentioning
confidence: 99%